ASSOCIATION OF NON-HDL CHOLESTEROL WITH RISK OF CARDIOVASCULAR DISEASE DEFINED BY TOTAL CHOLESTEROL/ HDL-CHOLESTEROL RATIO - B. PALLAVI,; KRISHNAMURTHY U,; RADHIKA.K, (International Journal of Pharma and Bio Sciences, 2016)
Non-HDL Cholesterol provides a single estimate of the cholesterol content in all proatherogenic lipoproteins. Total Cholesterol/ HDL-Cholesterol Ratio is a powerful predictor of cardiovascular disease (CVD). Therefore, this study was interested to find an association of non-HDL Cholesterol with risk of CVD defined by total Cholesterol/ HDL-Cholesterol Ratio. This study included 753 lipid profile data of adults collected for a period of 3 months. Lipid profile parameters were measured by enzymatic colorimetric method on a fasting venous sample. Non-HDL Cholesterol was calculated by subtracting the HDL Cholesterol from total cholesterol. Risk of CVD was defined by Total Cholesterol/ HDL-Cholesterol Ratio as ≥5. Sensitivity, specificity and cutoff of non-HDL Cholesterol for CVD was 70.9%, 71.5% and 137 mg/dl respectively. Non-HDL Cholesterol can be used as an economical and reliable parameter to assess the risk of CVD.